Fixed-bearing versus high-flexion RP total knee arthroplasty (TKA): midterm results of a randomized controlled trial - Amit Chaudhry; V. K. Goyal (Journal of Orthopaedics and Traumatology, 2018)
Abstract Background We compared the midterm results after total knee arthroplasty (TKA) using PFC Sigma RP-F mobile model with PFC Sigma PS fixed model. Materials and methods In this randomized controlled trial, we analyzed 50 knees that underwent TKA with PFC Sigma RP-F and 60 knees with PFC Sigma PS fixed model. The follow-up period ranged from 76 to 104 months. Results The knee score, function score, and radiographic evaluation were significantly not different between the two groups at final follow-up. No revisions, subluxations, dislocations, or infections were seen. Also, no radiographic evidence of component loosening, osteolysis, or malalignment was observed in any knee. The results for both groups show good patient satisfaction. Conclusions The midterm clinical and radiographic results of the two prostheses did not show significant differences between the two groups. Level of evidence Level of evidence is level II.